Method for producing spherical silica particles
The method addresses the cost and material availability issues in existing spherical silica particle production by using an alkaline aqueous silica solution with a basic substance in a mixed solvent, resulting in high-purity, cost-effective spherical silica particles with excellent filling properties.
Patent Information
- Application Number
- JP2024543668
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-08-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-08-30
AI Technical Summary
Existing methods for producing spherical silica particles, such as the stober method and emulsion synthesis, face challenges including high costs due to the use of expensive raw materials like TEOS, and the need for extensive washing to reduce sodium content from sodium silicate.
A method utilizing an alkaline aqueous silica solution as a raw material, where silica acid is dissolved in the presence of a basic substance with a quaternary ammonium or cyclic amidine structure in a mixed solvent of water and an organic solvent, followed by heating to remove organic matter and produce spherical silica particles.
This method allows for the production of spherical silica particles using cheaper and more readily available materials, such as metal silicon and silica, while achieving high purity and controlled particle size distribution, and excellent filling properties.
Smart Images

Figure 0007657374000003 
Figure 0007657374000004 
Figure 0007657374000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing spherical silica particles, and more particularly to a method for producing spherical silica particles by a so-called wet synthesis method. [Background technology]
[0002] There are three methods for producing silica particles with high sphericity: the melting method, the gas phase synthesis method, and the wet synthesis method. Among them, the wet synthesis method, represented by the Stober method, is characterized by the fact that it produces less coarse particles, but the particle size is highly uniform and the resin filling property is low. Furthermore, among the raw materials used in the Stober process, tetraethoxysilane (TEOS) is itself expensive, and in order to obtain particularly high-purity spherical silica particles, even higher-purity TEOS is required, which is even more expensive. One method for obtaining spherical porous silica is the emulsion synthesis method using sodium silicate as a raw material. However, the raw material contains a lot of sodium, and washing to reduce the amount increases the cost. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2021-195275 Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention has been completed in view of the above-mentioned circumstances, and an object of the present invention is to provide a novel method for producing spherical silica particles. [Means for solving the problem]
[0005] As a result of intensive research to solve the above problems, the inventors discovered that spherical silica particles can be produced using an alkaline aqueous silicic acid solution (hereinafter referred to as "alkaline aqueous silicic acid solution") as a raw material, and based on this finding, completed the following invention. That is, the method for producing spherical silica particles of the present invention includes the steps of: preparing a raw silica particle dispersion from a raw material solution in which silicic acid is dissolved in a mixed solvent of water and an organic solvent in the presence of a basic substance consisting of at least one of a quaternary ammonium salt and a base having a cyclic amidine structure; and a heating step of heating the dispersion or the raw silica particles obtained by solid-liquid separation from the dispersion to remove organic matter contained in the dispersion and prepare spherical silica particles. The mixed solvent has a relative dielectric constant of 21 to 40, and the quaternary ammonium derived from the basic substance is mixed in a molar ratio of 0.3 to 0.8 relative to the silicon element derived from the silicic acid. Effect of the Invention
[0006] The alkaline silicic acid aqueous solution can be prepared from materials such as metal silicon, silica, and TEOS, and it is possible to produce spherical silica particles from materials such as metal silicon and silica, which are often cheaper than TEOS. In addition, these materials are easily available in high purity, and the purity of the produced spherical silica particles can be easily improved. Furthermore, the particle size distribution of the obtained spherical silica particles can be controlled by the reaction conditions, and spherical silica particles with excellent packing properties can be produced. [Brief description of the drawings]
[0007] [Figure 1] 1 is a histogram showing particle size distributions of test samples of Test Examples 3, 5, 11, and 12 in the Examples. [Diagram 2] 1 is a SEM photograph of a test sample of Test Example 3 in the Examples. [Diagram 3] 1 is a SEM photograph of a test sample of Test Example 6 in the Examples. [Figure 4] 1 is a SEM photograph of a test sample of Test Example 8 in the Examples. [Diagram 5] 1 is a SEM photograph of a test sample of Test Example 10 in the Examples. [Figure 6]1 is a cross-sectional SEM photograph of a test sample of Test Example 11 in the Examples. [Figure 7] 1 is a SEM photograph of a test sample of Test Example 12 in the Examples. [Figure 8] 1 is a SEM photograph of a test sample of Test Example 14 in the Examples. [Figure 9] 1 is a SEM photograph of a test sample of Test Example 17 in the Examples. [Figure 10] 1 is a SEM photograph of a test sample of Test Example 18 in the Examples. [Figure 11] 1 is a cross-sectional SEM photograph of a test sample of Test Example 19 in the Examples. [Figure 12] 1 is a SEM photograph of a test sample of Test Example 20 in the Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The method for producing spherical silica particles of the present invention will be described in detail below based on the embodiment. The spherical silica particles produced by the method for producing spherical silica particles of this embodiment are particles with high sphericity and composed of silica. The spherical silica particles of this embodiment can be dispersed in a dispersion medium to form a slurry composition, or dispersed in a resin material to form a resin composition. These slurry compositions and resin compositions are preferably used as materials for electronic devices such as substrate materials, sealing materials, and underfills.
[0009] The spherical silica particles of this embodiment can be suitably produced with a particle size of about 100 nm to 10 μm. The sphericity of the spherical silica particles is not particularly limited, but is preferably 0.9 or more, and more preferably 0.95 or more.
[0010] The spherical silica particles may be solid or hollow. Here, the spherical silica particles are considered to be solid if their particle density is less than 2.3 g / cm 3 Hollow means that the particle has a density of 2.3 g / cm or more. 3This means that the particle density is less than 2.3 g / cm. In measuring particle density, the particle volume is measured by the constant volume expansion method using nitrogen. The volume measured includes voids into which nitrogen gas cannot penetrate, and the density of the particle is less than 2.3 g / cm. 3 Spherical silica particles with less than 100% voids are called hollow particles. The voids present inside the particle may be one or more. In addition, particles that are so-called porous with many extremely fine voids formed and where the voids cannot be observed even with an electron microscope are also called hollow particles.
[0011] The method for producing spherical silica particles according to the present embodiment includes a raw silica particle preparation step, a heating step, and other steps that may be adopted as necessary.
[0012] (Raw material silica particle preparation process) The raw silica particle preparation process is a process in which raw silica particles, which are the source of spherical silica particles, are precipitated from silicic acid contained in a raw solution in a mixed solvent of water and an organic solvent in the presence of a basic substance to form a dispersion. The precipitated raw silica particles are generally equivalent to the spherical silica particles produced, but contain a high content of moisture, organic matter, etc.
[0013] The precipitation of the raw silica particles is preferably carried out with stirring. The temperature during precipitation is not particularly limited, but the lower limit is 0°C, and the upper limit is 40°C, 50°C, or 60°C.
[0014] The concentration of silicic acid in the raw solution is not particularly limited, but based on the total mass, the lower limit can be 1%, 2%, 3%, or 5% in terms of oxide (SiO2: silica), and the upper limit can be 8%, 10%, 15%, or 17%. To obtain the required concentration, the solution can be diluted with water, an organic solvent, or a mixed solvent of water and an organic solvent. The oxide equivalent here is a value calculated on the assumption that all silicon elements contained are contained as oxides. The raw solution can contain other metal compounds other than silicic acid. Examples of other metal compounds that can be contained include water-soluble compounds and metal oxides with a particle size of 100 nm or less (particularly metal oxides with a particle size of 50 nm or less, 30 nm or less, or 10 nm or less). The other metal oxides can be incorporated when silicic acid precipitates and becomes particulate, forming composite oxides, etc.
[0015] In addition, the precipitation of the raw silica particles is preferably carried out in a state adjusted to a predetermined pH. The adjustment to the predetermined pH is preferably carried out by adding a basic substance or an organic acid such as acetic acid. The predetermined pH can be exemplified by lower limits of 7.0, 7.5, and 7.8, and upper limits of 10.0, 9.5, 9.0, 8.5, and 8.2.
[0016] Here, the mixed solvent has a relative dielectric constant of 21 or more and 40 or less. The upper limit of the relative dielectric constant may be 38, 35, or 33, and the lower limit may be 21.5, 23, or 25. These upper and lower limit values may be arbitrarily combined. Here, the relative dielectric constant of the mixed solvent is the relative dielectric constant calculated for the mixed solvent consisting of only the contained water and organic solvent. Specifically, it is calculated as a weighted average of the relative dielectric constant of water and the relative dielectric constant of the mixed organic solvent in terms of volume ratio.
[0017] The organic solvent is miscible with water and has a dielectric constant within the above range after mixing. Preferred organic solvents are ketones, esters, and alcohols, and in particular, acetone, methyl ethyl ketone, ethyl acetate, and the like can be used alone or as a mixture, and acetone is more preferably used. The mixing ratio of the organic solvent and water is set so that the mixed solvent has a dielectric constant within the above range.
[0018] The basic substance is at least one of a quaternary ammonium and a base having a cyclic amidine structure. Although they are not particularly limited, the quaternary ammonium is preferably selected from quaternary ammonium having 4 to 16 carbon atoms, and in particular, tetramethylammonium having 1 carbon atom, tetraethylammonium having 2 carbon atoms, and tetrabutylammonium having 4 carbon atoms can be exemplified. Quaternary ammonium usually has some anion as a counter ion. For example, tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), and tetrabutylammonium hydroxide (TBAOH) having hydroxide ions, and tetramethylammonium chloride, tetraethylammonium chloride, and tetrabutylammonium chloride having chloride ions can be exemplified. Examples of bases having a cyclic amidine structure include diazabicycloundecene (DBU) and diazabicyclononene (DBN).
[0019] The basic substance is contained in a ratio of 0.3 or more and 0.8 or less based on the number of moles of silicon element derived from silicic acid, and the lower limit can be 0.35, 0.4, and the upper limit can be 0.75, 0.7, 0.6. These upper and lower limits can be arbitrarily combined. By making the amount of basic substance added equal to or more than the lower limit, the particle size of the raw silica particles produced becomes large and aggregates are not formed, or the density of silica in the raw silica particles produced becomes high. By making the amount added equal to or less than the upper limit, oligomerization can be prevented and particle formation can be efficiently performed. If the density of silica is low, it tends to shrink when heated in the heating process described below, or the porosity of the obtained spherical silica particles when made into porous particles or hollow particles tends to be large.
[0020] The basic substance may be added to the mixed solvent before or after the silicic acid. Furthermore, the basic substance may be added in several portions rather than all at once. The concentration of silicic acid in the raw solution is not particularly limited, but the upper limit is preferably 0.1%, 0.2%, 0.3%, or 0.4%, and the lower limit is preferably 1.0%, 1.5%, 2.0%, or 3.0%, calculated as oxide based on the mass of the raw solution. The silicic acid is preferably supplied as an alkaline silicic acid aqueous solution obtained by any one of the following methods a) to c). These steps a) to c) are preferably performed with stirring. An appropriate amount of an organic solvent or a basic substance is added to the alkaline silicic acid aqueous solution obtained by the following steps to prepare the raw solution.
[0021] a) Heating and pressurizing silicon dioxide in an aqueous solution of a basic substance. Silicon dioxide can be synthesized from metal silicon, synthesized from silicon compounds, natural products, etc. In particular, silicon dioxide synthesized from metal silicon is preferred because it is easy to obtain high-purity metal silicon as the raw material. For example, powdered silicon dioxide obtained by a method of burning metal silicon powder (the so-called VMC method) can be used. Here, by using powdered silicon dioxide, the specific surface area becomes large, and the dissolution rate in an aqueous solution of a basic substance can be increased.
[0022] The basic substance contained in the aqueous basic substance solution for dissolving silicon dioxide may be the above-mentioned basic substance as it is, or other basic substances (other basic substances) may be used. When other basic substances are used, it is preferable to remove the other basic substances by washing or ion exchange after dissolving silicon dioxide.
[0023] Silicon dioxide can be dissolved in an aqueous solution of a basic substance by increasing the boiling point of the aqueous solution of the basic substance through pressure and maintaining the temperature at or above the boiling point at normal pressure. For example, heating at 180°C while applying pressure can be used. A higher dissolving temperature can improve the dissolving speed, while a lower temperature can reduce the pressure, simplifying the dissolving equipment. The silicon dioxide to be dissolved is preferably 17%, 15%, or 10% by weight, with the lower limit being 1%, 3%, or 5%, based on the total weight. These upper and lower limits can be combined in any way. The concentration of the basic substance in the aqueous basic substance solution is not particularly limited, but is preferably such that the basic substance has an appropriate concentration when the raw material solution is finally prepared.
[0024] b) Removal of Na ions from an aqueous sodium silicate solution in the presence of a basic substance. The sodium silicate aqueous solution can be prepared by dissolving sodium silicate in water or water glass. The basic substance can be any of the above-mentioned. By removing sodium ions from the sodium silicate aqueous solution in the presence of a basic substance, the sodium in the sodium silicate is replaced with a basic substance. The removal of sodium ions can be carried out using an ion exchange resin or the like. The sodium silicate to be dissolved is preferably set to an upper limit of 17%, 15%, or 10%, and a lower limit of 1%, 3%, or 5%, calculated as oxide based on the total mass. These upper and lower limits can be combined in any way. The concentration of the basic substance in the aqueous basic substance solution is not particularly limited, but is preferably set to a concentration that results in an appropriate basic substance concentration when the raw material solution is finally prepared.
[0025] c) Dissolution of metallic silicon in an aqueous solution containing a basic substance and / or a second basic substance. Silica is produced by immersing and dissolving metallic silicon in an aqueous solution in which the above-mentioned basic substance and / or second basic substance is dissolved. The metallic silicon is preferably in the form of powder or granules. Heating is preferable as a dissolving condition. The heating temperature is not particularly limited, but the lower limit may be 30°C, 40°C, 50°C, 60°C, etc.
[0026] The amount of metal silicon to be dissolved is preferably 17%, 15%, or 10% in terms of oxide based on the total mass, and the lower limit is preferably 1%, 3%, or 5%. These upper and lower limits can be combined in any desired manner.
[0027] The basic substance is the same as the basic substance described above. The second basic substance is not particularly limited, but is preferably an organic substance. Examples of the second basic substance include dialkylamines (e.g., those having 1 to 3 carbon atoms) and trialkylamines (e.g., those having 1 to 3 carbon atoms).
[0028] The total concentration of the basic substance and the second basic substance in the aqueous solution containing the basic substance and / or the second basic substance is not particularly limited. When the basic substance is added, the concentration is preferably such that the amount of the basic substance present is equal to or less than the appropriate amount when the raw solution is finally prepared.
[0029] (Heating process) The heating step is a step of heating the raw silica particles contained in the dispersion liquid obtained in the raw silica particle preparation step to form spherical silica particles, and is a step of removing moisture and organic matter contained in the raw silica particles by heating.
[0030] The heating step is performed by heating the dispersion as it is, the dispersion medium of which has been replaced with another dispersion medium, and / or the raw silica particles from the dispersion after solid-liquid separation. The raw silica particles can be separated from the dispersion medium by centrifugation or filtration. After separating the raw silica particles, the dispersion medium can be replaced by adding another dispersion medium such as water or an organic solvent. By replacing the dispersion medium multiple times, organic substances contained in the dispersion can be removed more reliably.
[0031] In the heating step, moisture and organic matter contained in the raw silica particles can be removed by heating at a high temperature. First, it is preferable to remove moisture and organic solvents at a temperature at which moisture is not rapidly removed. For example, 40°C, 60°C, 80°C, 100°C, 120°C, 140°C, etc. The pressure can be reduced or air-dried at the same time as heating. If moisture can be removed to a certain extent, rapid expansion of moisture will not occur even if the material is heated at a high temperature, so the material is heated to a temperature at which the organic matter can be removed. A temperature of 500°C or higher is preferable as a temperature at which the organic matter can be removed.
[0032] In particular, heating in an oxidizing atmosphere such as air is preferable because organic matter can be oxidized and removed. The lower limit of the heating temperature can be 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, etc., and the upper limit can be 1150°C, 1100°C, 1050°C, etc. It is believed that by heating the raw silica particles in a state separated from the dispersion medium, the particles shrink and become dense as moisture is removed.
[0033] (hydrothermal treatment process) After the raw silica particle preparation step and before the heating step, it is preferable to have a hydrothermal treatment step in which the dispersion medium of the dispersion is replaced with water and then heated to proceed with a hydrothermal reaction. The hydrothermal reaction is preferably carried out at a temperature of 130°C or higher and 250°C or lower. In particular, it is preferable to adopt a lower limit of 100°C, 110°C, or 120°C, and an upper limit of 220°C, 200°C, or 180°C. These upper and lower limits can be combined arbitrarily.
[0034] By carrying out a hydrothermal reaction, the spherical silica particles finally produced can be made into hollow or porous particles. In other words, the hydrothermal treatment process causes a reaction in which the parts of the inside of the particles with low silanol bond density are dissolved by a basic substance, and a reaction in which the outer shell of the particles is densified by heat to occur in equilibrium, and it is presumed that the hollow or porous particles are produced by the balance of these two reactions.
[0035] When a hydrothermal treatment step is performed, the raw silica particles are then separated from the dispersion medium and heated to remove organic matter as described above. When a hydrothermal reaction is performed, it is particularly preferable to heat the raw silica particles to 900° C. or higher in the heating step to strengthen the hollow particles or porous particles.
[0036] (Other processes) In the method for producing spherical silica particles according to the present embodiment, the obtained spherical particles can be crushed or surface-treated. Crushing can be performed by a method similar to a normal grinding operation. In particular, it is preferable to use a jet mill or the like.
[0037] The spherical silica particles produced by the method for producing spherical silica particles of this embodiment can be surface-treated with a surface treatment agent such as a silane compound. The appropriate surface treatment varies depending on the form of use of the spherical silica particles. When filling the spherical silica particles in a resin, it is preferable to use a surface treatment agent that can introduce a functional group that has high affinity or reactivity with the resin. EXAMPLES
[0038] The method for producing spherical silica particles of the present invention will be described in detail below with reference to examples.
[0039] <Sample preparation> Test samples for each test example were prepared under the conditions shown in Table 1. The details are explained below. Test Example 1 (Raw material silica particle preparation process) First, an alkaline silicic acid aqueous solution was prepared by mixing 9.0 g of metallic silicon powder (volume average particle size 20 μm), 27.0 g of ion-exchanged water, and 64.0 g of a 25 mass% TMAH aqueous solution, and then keeping the mixture at 40° C. for 48 hours to dissolve the metallic silicon, thereby obtaining an alkaline silicic acid aqueous solution containing approximately 26.3% silicic acid in terms of silica.
[0040] Ion-exchanged water was added to the obtained alkaline silicic acid aqueous solution so that the silicic acid concentration was 4.5 mass% in terms of silica. TMAH was added so that the amount of TMAH present as a basic substance was 0.44 in total molar ratio based on the silicon element derived from the contained silicic acid. Then, acetone was added so that the molar ratio when mixed with water containing the organic solvent was 30.6. Specifically, the ratio of water:acetone was 20:80 in mass ratio before mixing.
[0041] After thorough stirring, a 90% by mass aqueous solution of acetic acid was added to adjust the pH to 8, and stirring was continued for an additional 30 minutes, causing the raw silica particles to precipitate and become a dispersion.
[0042] (Heating process) The obtained dispersion was centrifuged at 5000 rpm for 5 minutes, and the supernatant was removed by decantation to separate the precipitate. Centrifugation was performed using Model 3700 manufactured by KUBOTA. The same mass of ion-exchanged water as the removed supernatant was added and ultrasonic dispersion was performed. Ultrasonic waves were applied for 30 minutes at a frequency of 28 kHz and 1000 W. Centrifugation was performed again under the above conditions, and the obtained precipitate was dried at 130 ° C for 1 hour and then fired at 500 ° C for 2 hours. The obtained fired product was crushed in a mortar until the aggregates could no longer be seen with the naked eye, and the obtained spherical silica particles were used as the test sample of this test example.
[0043] Test Examples 2 and 3 Test samples of these test examples were obtained by carrying out the same operations as in Test Example 1, except that the firing temperature was 800° C. (Test Example 2) and 1000° C. (Test Example 3).
[0044] Test Examples 4 and 5 The test samples of this test example were obtained by the same procedure as in Test Example 1, except that a) the amount of basic substance present was 0.55 in molar ratio based on the silicon element derived from silicic acid, b) the heating process included a hydrothermal treatment process in which the dispersion obtained by ultrasonic dispersion after the first centrifugation was placed in a pressure vessel and subjected to a hydrothermal reaction at 175°C for 2 hours, and c) the firing temperature was 800°C (Test Example 4) and 1000°C (Test Example 5).
[0045] Test Examples 6-9 A test sample of this test example was obtained in the same manner as in Test Example 5, except for the following differences. a) The amount of basic substance present was adjusted to 0.44 in molar ratio based on the silicon element derived from silicic acid, b) the pH was set to 6 (Test Example 6), the pH was set to 6 and the temperature during the hydrothermal reaction was set to 200°C (Test Example 7), and only a) was changed (Test Example 8), the pH was set to 6 and the temperature during the hydrothermal reaction was set to 121°C (Test Example 9).
[0046] Test Examples 10 and 11 The test samples of this test example were obtained by the same procedure as in Test Example 3, except that the amount of basic substance present was 0.35 (Test Example 10) and 0.79 (Test Example 11) in molar ratio based on the silicon element derived from silicic acid.
[0047] Test Example 12 (Equivalent to the raw silica particle preparation process) A mixture of 5.2g of TEOS, 100g of ion-exchanged water, and 400g of acetone was prepared. 2.5g of 25% by mass TMAH aqueous solution was added to this mixture while stirring. Then, 90% by mass acetic acid aqueous solution was quickly added to adjust the pH to 8, and stirring was continued for another 30 minutes, causing the raw silica particles to precipitate and become a dispersion. The ratio of ion-exchanged water to acetone was set so that the relative dielectric constant was 30.6. The amount of TMAH added was 1.0g, which is the amount of TMAH derived from TEOS. Noke The molar ratio was set to 0.27 based on elemental iron.
[0048] (corresponding to the heating process) The obtained dispersion was centrifuged at 5000 rpm for 5 minutes, and the supernatant was removed by decantation to separate the precipitate. Centrifugation was performed using a KUBOTA Model 3700. Ion-exchanged water of the same mass as the removed supernatant was added and ultrasonic dispersion was performed. Ultrasonic waves were applied at a frequency of 28 kHz and 1000 W for 30 minutes.
[0049] The obtained dispersion was placed in a pressure vessel and subjected to a hydrothermal reaction at 175° C. for 2 hours. Then, the dispersion was centrifuged again under the above-mentioned conditions, and the obtained precipitate was dried at 130° C. for 1 hour and then fired at 1000° C. for 2 hours. The fired product was crushed in a mortar until agglomerates could no longer be seen with the naked eye, and the obtained spherical silica particles were used as the test sample for this test example.
[0050] Test Example 13 The same operation as in Test Example 3 was carried out, except that the content of acetone was set to an amount that would be 20 when mixed with the water contained. As a result, no particle generation was observed in the process corresponding to the raw silica particle preparation process, and no heating process was performed. Therefore, no test sample for this test example was obtained.
[0051] Test Example 14 A test sample for this test example was obtained in the same manner as in Test Example 3, except that the acetone content was an amount that became 41.5 when mixed with the contained water.
[0052] Test Example 15 A test sample for this test example was obtained in the same manner as in Test Example 1, except that the amount of the basic substance present was 0.20 in molar ratio based on the silicon element derived from silicic acid.
[0053] Test Example 16 The same operation as in Test Example 1 was carried out, except that the amount of basic substance present was set to 0.85 in molar ratio based on the silicon element derived from silicic acid. As a result, no particle generation was observed in the process corresponding to the raw silica particle preparation process, and no heating process was carried out. Therefore, no test sample for this Test Example was obtained.
[0054] Test Examples 17 and 18 Test samples of this Test Example were obtained by the same procedure as Test Example 5, except that DBU (Test Example 17) and DBN (Test Example 18) were used instead of TMAH as the basic substance. The amounts of DBU and DBN added were the same as those of TMAH. As a result, the amounts of DBU and DBN added were adjusted so that the amount of basic substance present was 0.41 in molar ratio based on the silicon element derived from silicic acid.
[0055] Test Examples 19 and 20 Test samples of this test example were obtained by the same procedure as in Test Example 3, except that TEAH (Test Example 19) and TBAOH (Test Example 20) were used instead of TMAH as the basic substance. The amounts of TEAH and TBAOH added were adjusted to have the same concentrations as TMAH. As a result, the amounts of TEAH and TBAOH added were adjusted so that the amount of basic substance present was 0.32 (Test Example 19) and 0.35 (Test Example 20) in molar ratio based on silicon element derived from silicic acid.
[0056] Test Example 21 In Test Example 1, in the raw silica particle preparation process The metallic silicon powder, which was the raw material for producing the alkaline silicic acid aqueous solution, was used to prepare spherical silica particles by the VMC method, which was used as the test sample for this test example. The VMC method is a method for producing spherical silica particles by deflagrating metallic silicon powder suspended in air.
[0057] (evaluation) The test samples of each test example were measured for particle size distribution, specific surface area, pore volume, true specific gravity, coarse particle evaluation, and impurity content. The results are shown in Tables 1 and 2.
[0058] Particle size distribution: The test sample was dispersed in water at a concentration of 0.5% by mass, and the particle size distribution was measured using a particle size distribution measuring device (Shimadzu SALD-7500 nano). For Test Examples 3, 5, 11, and 12, the histograms of the measured particle size distribution are shown in Figure 1.
[0059] Specific surface area, pore volume: The test samples were measured using an automatic specific surface area / pore distribution measuring device (Shimadzu Tristar 3000). The specific surface area was measured by the BET single point method using nitrogen gas. The pore volume was measured using the value at the time of adsorption measured using the BJH method.
[0060] True specific gravity: measured with a dry automatic density meter (Shimadzu Corporation, Accupic II 1345) in nitrogen gas The density was measured using the particle volume including the voids inside the spherical silica particles into which nitrogen gas cannot penetrate. In other words, if voids exist, the density of the spherical silica particles decreases by the volume of the voids.
[0061] Evaluation of coarse particles: For each of the test samples of Test Examples 3, 5, and 21, the number of particles with a diameter of 3 μm or more contained per gram was measured using an automatic flow type particle imaging analyzer (Sysmex, FPIA-3000).
[0062] Impurity content: For each of the test samples of Test Examples 5 and 21, the test sample was dissolved in acid and then the impurity content was measured by ICP. Furthermore, SEM photographs were taken of each of the test samples of Test Examples 3, 6, 8, 10 to 12, 14, and 17 to 20 (FIGS. 2 to 12). [Table 1]
[0063] [Table 2]
[0064] As is clear from Table 1, the three groups, a) Test Examples 1 to 3, b) Test Examples 4 and 5, and c) Test Examples 6 to 9, had the same conditions before firing within each group and the same particle size distribution within each group, but the heating conditions in the subsequent heating process were different within each group, resulting in different specific surface area values.
[0065] In other words, when the conditions of the raw silica particle preparation process are the same, spherical silica particles with the same particle size distribution are obtained. In the subsequent processing step, the specific surface area differs depending on the heating temperature (temperature during hydrothermal reaction, firing temperature) after removing the dispersion medium. The reason for the difference in specific surface area is thought to be due to the change in the pore structure of the produced spherical silica particles, especially the pore structure on the surface.
[0066] In Test Example 12, in which spherical silica particles were produced from TEOS, the particle size was uniform, whereas the particle size distribution was broad in the test samples of Test Examples 1 to 11 and 17 to 20, in which spherical silica particles were produced via silicic acid. Specifically, it was found that the test sample of Test Example 12 had a very uniform particle size. The fact that the particle size distribution of the particles in Test Example 12 was uniform is supported by the fact that D90 / D50 was about 1.26, and also by the SEM photograph shown in FIG. 7.
[0067] In contrast, the test samples of Test Examples 1 to 11 and 17 to 20 contained particles of various particle sizes, with the smallest D90 / D50 being 1.67 in Test Examples 4 and 5. In addition, as is clear from Figures 2 to 6 and Figures 8 to 12, the particle sizes are not uniform.
[0068] Therefore, it is expected that the test samples of Test Examples 1 to 11 and 17 to 20 will have improved filling properties in resins, slurries, etc. This is also evident from the histogram shown in Figure 1, which shows that the test sample of Test Example 12, which used TEOS as a raw material, has a uniform particle size, but the test samples of Test Examples 3, 5, and 11 have particle size variations.
[0069] The specific gravity of silica is 2.3g / cm 3 The true density of Test Examples 1 to 3, 10, 11, 19, and 20, which were not subjected to a hydrothermal reaction, was 2.3 g / cm 3 It was inferred that there were no voids inside. In contrast, the true specific gravity of Test Examples 4 to 6, 17, and 18, which were subjected to a hydrothermal reaction, was 2.3 g / cm 3 It was found that the internal voids were smaller than the above and did not communicate with the outside.
[0070] Among the test samples undergoing the hydrothermal reaction, the true specific gravity of Test Examples 7 to 9 was 2.3 g / cm 3 The true specific gravity is equivalent to that of particles without voids, but as is clear from the large pore volume and specific surface area of these test samples, the voids that were generated are connected to the outside, which is thought to have made the true specific gravity the same as that of silica.
[0071] The presence or absence of voids (pores) communicating with the outside due to differences in preparation conditions can also be confirmed by SEM photographs. As is clear from FIG. 2, the presence of voids (pores) communicating with the outside was not observed in the test sample of Test Example 3. As is clear from FIG. 3, the test sample of Test Example 6 included particles with pores, but as a whole it was confirmed that there were generally no pores. In contrast, as is clear from FIG. 4, the test sample of Test Example 8 contained a majority of particles with pores.
[0072] In other words, in the test sample of Test Example 8, voids were formed inside like hollow particles, but because these voids were connected to the outside, it was found that the true specific gravity was the same as that of solid particles. Furthermore, although details are not shown, when the cross section of the test sample of Test Example 5 was examined, it was found that many voids were formed in a porous state. The density of the fine voids tended to increase as it approached the center of the particle.
[0073] The mechanism by which internal voids are created by using a hydrothermal reaction is presumed to be as follows: When raw silica particles are converted into spherical silica particles by carrying out a hydrothermal reaction, moisture is slowly released from the outside, causing the outside of the particles to become dense, and then voids are created inside when moisture is released from the inside, but when firing is carried out by rapid heating without a hydrothermal reaction, moisture is released suddenly from the entire particle and it is fired, resulting in solid particles with no internal voids.
[0074] It was found that when the relative dielectric constant of the mixed solvent of water and an organic solvent was 20 (Test Example 13), the silicic acid contained in the raw material solution was dissolved as it was without precipitating. Therefore, it was found that the relative dielectric constant of the mixed solvent must be at least 20 or more.
[0075] When the relative dielectric constant of the mixed solvent of water and an organic solvent was set to 41.5 (Test Example 14), the silicic acid contained in the raw solution did not form particles when it precipitated, but only formed fine silica aggregates (Figure 8). Therefore, it was found that the relative dielectric constant of the mixed solvent must be at least 41.5 or less.
[0076] In Test Example 15, in which the amount of basic substance added was 0.20 in molar ratio to the silicon element derived from silicic acid, the silicic acid contained in the raw solution did not become particles when it precipitated, but only formed fine silica aggregates. Therefore, it was found that the amount of basic substance added must exceed 0.20 in molar ratio to the silicon element derived from silicic acid.
[0077] In Test Example 16, in which the amount of the basic substance added was 0.85 in molar ratio to the silicon element derived from silicic acid, it was found that the silicic acid contained in the raw solution was dissolved as it was without precipitating. Therefore, it was found that the amount of the basic substance added must be less than 0.85 in molar ratio to the silicon element derived from silicic acid.
[0078] It was found that even when DBU (Test Example 17), DBN (Test Example 18), TEAH (Test Example 19), or TBAOH (Test Example 20) were used instead of TMAH as the basic substance, spherical silica particles could be produced similarly to the case of TMAH (Figures 9 to 12).
[0079] The number of coarse particles was measured for Test Examples 3, 5, and 21. As a result, it was found that while the spherical silica particles of Test Example 21, which were produced by the conventional VMC method, had more than 2,000 coarse particles, the number of coarse particles was extremely small, at 5 and 36, respectively, for Test Examples 3 and 5.
[0080] The impurity contents of Test Examples 5 and 21 were measured, and it was found that the contents of Th and U were reduced to less than one tenth of those of the spherical silica particles of Test Example 21 produced by the conventional VMC method, and that the effects of alpha rays when used in electronic devices can be reduced. In addition, the contents of the other measured elements also tended to generally decrease. This is presumably because in Test Example 5, the impurities did not precipitate when the metallic silicon powder was dissolved once and then precipitated.
[0081] (Other exams) In the above test examples, metallic silicon powder was used as the raw material for preparing the alkaline silicic acid aqueous solution, but it was confirmed that spherical silica particles could also be produced by using other materials, such as silica particles and water glass (aqueous sodium silicate solution).After preparing the alkaline silicic acid aqueous solution from each of the materials, silica and sodium silicate aqueous solution, the same spherical silica particles as those using metallic silicon powder could be obtained by carrying out the same operations as those using metallic silicon powder.
[0082] -Method using silica particles 20.0 g of silica powder (product name: SO-E2, manufactured by Admatechs Co., Ltd.), 15.0 g of ion-exchanged water, and 64.0 g of a 25% by mass TMAH aqueous solution were mixed and held at 180°C for 1 hour in a pressure vessel to dissolve the silica, thereby obtaining an alkaline silicic acid aqueous solution containing approximately 20.2% silicic acid in terms of silica.
[0083] Method using sodium silicate solution 10.2 g of sodium silicate aqueous solution (water glass) and 15.0 g of ion-exchanged water were mixed and stirred at 40° C. for 4 hours. Then, 64.0 g of 25% by mass TMAH aqueous solution was added dropwise to remove Na ions by ion exchange. As a result, an alkaline silicic acid aqueous solution containing 10.8% by mass of silica was obtained.
Claims
1. a raw silica particle preparation step of preparing a dispersion of raw silica particles from a raw material solution in which silicic acid is dissolved in a mixed solvent of water and an organic solvent in the presence of a basic substance consisting of at least one of a quaternary ammonium salt and a base having a cyclic amidine structure; a heating step of heating the dispersion or the raw silica particles obtained by solid-liquid separation from the dispersion to remove organic matter contained in the dispersion and prepare spherical silica particles; having The mixed solvent has a relative dielectric constant of 21 or more and 40 or less, A method for producing spherical silica particles, wherein the basic substance is mixed in a molar ratio of 0.3 or more and 0.8 or less with respect to the silicon element derived from the silicic acid.
2. 2. The method for producing spherical silica particles according to claim 1, wherein the organic solvent is one or more solvents selected from the group consisting of acetone, methyl ethyl ketone, and ethyl acetate.
3. 3. The method for producing spherical silica particles according to claim 1, wherein the basic substance is at least one compound selected from the group consisting of quaternary ammonium having 4 to 16 carbon atoms, diazabicycloundecene, and diazabicyclononene.
4. The raw material solution is a) heating and pressurizing silicon dioxide in the aqueous solution of a basic substance; b) removing Na ions from the aqueous sodium silicate solution in the presence of the basic substance; and c) dissolving metallic silicon in an aqueous solution containing the basic substance and / or the second basic substance; For an alkaline silicic acid aqueous solution obtained by any one of the methods of The method for producing spherical silica particles according to claim 1 or 2, wherein the spherical silica particles are prepared by a raw material solution preparation step of adding the organic solvent and the basic substance, which is added as necessary, so as to obtain the blending ratio.
5. 3. The method for producing spherical silica particles according to claim 1, wherein the raw silica particle preparation step is a step of preparing the raw silica particles by adjusting the pH of the raw solution to 7 or more and 10 or less.
6. a hydrothermal treatment step of replacing a dispersion medium for dispersing the raw silica particles with water after the raw silica particle preparation step and before the heating step, and then pressurizing and heating the raw silica particles to 130° C. or more and 250° C. or less; The method for producing spherical silica particles according to claim 1 or 2, wherein the spherical silica particles produced in the heating step are hollow particles.
7. The method for producing spherical silica particles according to claim 6 , wherein the heating step includes a step of heating at 900° C. or higher.
Citation Information
Patent Citations
Method for producing spherical silica-based mesoporous body
JP2006027985A
Method for manufacturing anisotropic-shape silica sol
JP2007153671A
Method for producing hollow silica particles
JP2021195275A
Method for manufacturing metal-oxide-containing particles and method for manufacturing aggregate of metal-oxide colloidal particles
WO2012096172A1
Spherical silica particles
WO2024047769A1